2012
DOI: 10.1007/s10495-011-0682-1
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in extracorporeal preserved inguinal fat flaps of the rat

Abstract: Fat cells are fragile cells with a short life span outside the body. Ways to reduce cell death in a biochemical way are almost unknown due to scarce information on the type of cellular death that is induced in fat tissue. This study was designed to investigate the apoptotic pathways of fat tissue in a permanent perfusion bioreactor system with the Hannover preservation solution and the Eurocollins solution in fat flaps of rats. In Lewis rats, the inguinal adipofascial flaps were elevated bilaterally and placed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…27,28 Cleaved caspase 3-cleaved caspases 8, 9, and 12 were detected in adipose tissue as an effector of the common apoptotic pathway, and Bcl-2 and Bcl-XL were found in the adipose tissue. 29,30 Also, it is well known that minocycline, a tetracycline derivative, suppresses apoptosis via controlling glutamate-induced apoptosis, upregulates Bcl-2, and protects against cell death in mitochondria and inhibits caspase-1 and caspase-3 expression or interleukin 1-converting enzyme inhibition. [15][16][17][18][19][20][21][22] In light of these data, we applied systemic minocycline 2 hours before fat graft application.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Cleaved caspase 3-cleaved caspases 8, 9, and 12 were detected in adipose tissue as an effector of the common apoptotic pathway, and Bcl-2 and Bcl-XL were found in the adipose tissue. 29,30 Also, it is well known that minocycline, a tetracycline derivative, suppresses apoptosis via controlling glutamate-induced apoptosis, upregulates Bcl-2, and protects against cell death in mitochondria and inhibits caspase-1 and caspase-3 expression or interleukin 1-converting enzyme inhibition. [15][16][17][18][19][20][21][22] In light of these data, we applied systemic minocycline 2 hours before fat graft application.…”
Section: Discussionmentioning
confidence: 99%
“…At this time, the standard procedure in reconstructive surgery for flap preservation is cold storage, often in addition with a singular flush of the tissue with a saline solution. In the past, numerous studies have been set‐up to learn more about causes of ischaemia‐related tissue damage and optimizing conservation protocols . Even though most of these studies revealed encouraging results, at present none of them essentially changed the standard procedure in daily clinical routine.…”
Section: Introductionmentioning
confidence: 99%
“…In eigenen Arbeiten konnte ge zeigt werden, dass in Fettgewebe Apop tose über verschiedene Apoptosewege stattfinden kann [9]. Apoptosewege über Mitochondrien, das Endoplasmatische Retikulum und death receptor vermittelt, die mit einer Aktivierung der Caspasen 3,8,9 und 12 einhergehen, wurden darge stellt [10]. In histologischen Arbeiten zur Kälteanwendung auf Fettgewebe konnte gezeigt werden, dass eine inflammatori sche Antwort auf die Kälteexposition ab läuft, mit einem Höhepunkt am 30.…”
unclassified